Penerapan Metode Random Forest dalam Pengklasifikasian Penerima Kartu BPJS Kesehatan Penerima Bantuan Iuran (PBI) di Kabupaten Karangasem, Provinsi Bali 2017 - Qonita Raihananda; I Wayan Edy Darma Putra; Monica Seftaviani Sijabat; Sifa Rofatunnisa; Ibnu Maruf; Hermarwan Hermarwan; Rani Nooraeni (Department of Mathematics, Hasanuddin University, 2021)
BPJS Kesehatan is a social security facility provided by the government to all people who are registered as members. BPJS Kesehatan membership is divided into two, namely BPJS for Contribution Assistance Recipients (BPJS PBI) and BPJS Non-Contribution Assistance Recipients (BPJS Non-PBI). In 2019, Bali Province is targeted to achieve Universal Health Coverage of 95 percent so that the Bali Provincial Government has budgeted funds worth IDR 945 billion to finance JKN - KBS services which are integrated with JKN - KIS. Karangasem is one of the four districts in Bali Province that received the most percentage of financing, which is 51 percent of the total budget needed when compared to other areas. This study aims to classify the BPJS-PBI recipient community based on education variables, employment indicators, age, and per capita expenditure in Karangasem Regency in 2017. The classification method used in this study is the random forest method. The results showed that the per capita expenditure variable had the largest contribution in classifying the status of PBI participants. The model that is formed produces an accuracy of 0.8017. This means that the model can predict 80.17 percent testing data correctly.